Penggunaan Ethnomatematika Engklek Dalam Pembelajaran Matematika - Ari Irawan (Jurnal MathEducation Nusantara, 2018)
Abstract The study aims to reveal the elements of mathematics contained in the game that is a traditional game. The research method used is survey explorative with qualitative approach. Instruments used in the form of interviews, direct observation / observation, literature studies and consultation with experts etnomatematics. The study found that in the cradle of the mathematical element in the form of flat geometry, the original number, useful for fine motor training, and to train character education in children from an early age in the form of honesty, discipline and togetherness. Keywords: Ethnomatematics, Engklek, Traditional, Games, Mathematics